2018
DOI: 10.1002/aet2.10203
|View full text |Cite
|
Sign up to set email alerts
|

Critical Appraisal of Emergency Medicine Educational Research: The Best Publications of 2016

Abstract: Objectives: The objectives were to critically appraise the emergency medicine (EM) medical education literature published in 2016 and review the highest-quality quantitative and qualitative studies. Methods: A search of the English language literature in 2016 querying MEDLINE, Scopus, Education ResourcesInformation Center (ERIC), and PsychInfo identified 510 papers related to medical education in EM. Two reviewers independently screened all of the publications using previously established exclusion criteria. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 158 publications
0
8
0
Order By: Relevance
“…We piloted the final quantitative research rubric by scoring abstracts from publications identified in the most recent critical appraisal of EM education research by Academic Emergency Medicine/AEM Education and Training, "Critical Appraisal of Emergency Medicine Education Research: The Best Publications of 2016". 18 All 11 papers highlighted for excellent methodology in this issue were included in the pilot. 18 Additionally, we included an equal number of randomly selected citations that were included in the issue but not selected as top papers, for a total of 22 quantitative publications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We piloted the final quantitative research rubric by scoring abstracts from publications identified in the most recent critical appraisal of EM education research by Academic Emergency Medicine/AEM Education and Training, "Critical Appraisal of Emergency Medicine Education Research: The Best Publications of 2016". 18 All 11 papers highlighted for excellent methodology in this issue were included in the pilot. 18 Additionally, we included an equal number of randomly selected citations that were included in the issue but not selected as top papers, for a total of 22 quantitative publications.…”
Section: Discussionmentioning
confidence: 99%
“…18 All 11 papers highlighted for excellent methodology in this issue were included in the pilot. 18 Additionally, we included an equal number of randomly selected citations that were included in the issue but not selected as top papers, for a total of 22 quantitative publications. 18 Given the limited number of qualitative studies cited in this issue of the critical appraisal series, we chose to pilot the qualitative rubric on publications from this series from the last 5 years available (2012-2016).…”
Section: Discussionmentioning
confidence: 99%
“…External funding has been shown to be a crucial step toward the maturation of successful investigators and increasing the knowledge base complexity of publications . One series of articles evaluating EM education research found that the number of funded studies increased from 16% in 2014 to 20% in 2015, although this declined to 11% in 2016 . We conducted a review of all publications from 2018 and 2019 in AEM Education and Training and found that 34% of original manuscripts had reported some form of funding.…”
Section: Advances In Medical Education Scholarshipmentioning
confidence: 94%
“…In the years since the conference, our field has seen significant growth in education research training opportunities, EM specialty‐specific venues for publishing education scholarship, and prominence of EM education research leaders in national medical education arenas . The topics pursued by EM education researchers have also evolved substantially since 2012 in response to programmatic changes such as the Accreditation Council for Graduate Medical Education (ACGME) milestones project and the influences of novel modalities for education, assessment, and evaluation …”
Section: Specific Objectives Of the 2012 Academic Emergency Medicine mentioning
confidence: 99%
See 1 more Smart Citation